2015
DOI: 10.1080/00036846.2015.1058906
|View full text |Cite
|
Sign up to set email alerts
|

What drives the reversal of the gender education gap? Evidence from Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…In the same period, girls also made gains relative to boys on standardized math and reading tests (Goldin, Katz, and Kuziemko, 2006;Cho, 2007) and grades (Fortin, Oreopoulos, and Phipps, 2015). Previous research has found evidence that boys are more sensitive than girls with respect to both parental (Bertrand and Pan, 2013;Riphahn and Schwientek, 2015) and school/preschool inputs (Krueger, 1999;Machin and McNally, 2008;Chetty et al, 2011;Havnes and Mogstad, 2011). This is supported by evidence showing that boys benefit more strongly than girls from early childhood interventions (Campbell et al, 2014;Conti, Heckman, and Pinto, 2015) and are more impatient (Bettinger and Slonim, 2007;7 Dohmen, Falk, and Sunde, 2010;Castillo, Ferraro, Jordan, and Petrie, 2011;Golsteyn, Grönqvist, and Lindahl, 2014).…”
supporting
confidence: 69%
“…In the same period, girls also made gains relative to boys on standardized math and reading tests (Goldin, Katz, and Kuziemko, 2006;Cho, 2007) and grades (Fortin, Oreopoulos, and Phipps, 2015). Previous research has found evidence that boys are more sensitive than girls with respect to both parental (Bertrand and Pan, 2013;Riphahn and Schwientek, 2015) and school/preschool inputs (Krueger, 1999;Machin and McNally, 2008;Chetty et al, 2011;Havnes and Mogstad, 2011). This is supported by evidence showing that boys benefit more strongly than girls from early childhood interventions (Campbell et al, 2014;Conti, Heckman, and Pinto, 2015) and are more impatient (Bettinger and Slonim, 2007;7 Dohmen, Falk, and Sunde, 2010;Castillo, Ferraro, Jordan, and Petrie, 2011;Golsteyn, Grönqvist, and Lindahl, 2014).…”
supporting
confidence: 69%
“…Women are more likely to pursue a university degree in industrised countries (Becker et al, 2010;Parro, 2012;Riphahn and Schwientek 2015;Wells et al, 2013) and greater interest in higher education among women has frequently been cited as a major cause of gender imbalances in rural areas (Corbett, 2007;Lowe, 2015;Rauhut and Littke, 2016;Stenbacka, 2008). Similar conclusions have been drawn in the Icelandic context (Gislason and Olafsson 2006).…”
Section: Discussionmentioning
confidence: 61%
“…and Pan (2013), , Owens (2016), Prevoo and ter Weel (2014), Karbownik and Myck (2017), Riphahn and Schwientek (2015), and Woessmann (2015) focus on the role of family and schooling environment in generating observed gender gaps in behavioral and educational outcomes. 11 Bertrand and Pan (2013) offer the most complete extant analysis of the relationship between family background and gender differences in early childhood outcomes.…”
Section: Introductionmentioning
confidence: 99%